Perceptions of functional tax advisors on artiicial intelligence-based applications in the context of performance improvement efforts - Khusnaini, Khusnaini; Liyana, Nur Farida; Ambarwati, Ria Dewi (Educoretax, 2024)
This study aims to analyze the influence of perceived usefulness and perceived ease of use of Artificial Intelligence (AI)-based applications on the willingness of functional tax instructors to use these AI-based applications. The data used in this study are primary data from questionnaire surveys distributed to functional tax extension officers from all Regional Offices of the Directorate General of Taxes from October to December 2023. In addition, this study also uses secondary data sourced from regulatory documents and other data related to the performance of tax extension officers from the Directorate General of Taxes. Data from 104 respondents were analyzed using multiple linear regression. This study concludes that the perceived usefulness and perceived ease of use of AI-based applications have a positive and significant effect on the willingness of Functional Tax Instructors to use AI-based applications. Functional extension workers need to continue to try to work side by side with technology so that work becomes faster and easier. With the help of AI technology, it is not impossible that the implementation of taxation counseling can be partially delegated to technological assistance so that tax education can be more massive and comprehensive.